Phase I study evaluating the treatment of patients with locally advanced pancreatic cancer with carbon ion radiotherapy: The PHOENIX-01 trial - Combs, Stephanie E.; Habermehl, Daniel; Kieser, Meinhard; Dreher, Constantin; Werner, Jens; Haselmann, Renate; Jaekel, Oliver; Jaeger, Dirk; Buechler, Markus W.; Debus, Juergen (BMC Cancer, 2013)
Background: Treatment options for patients with locally advanced pancreatic cancer include surgery, chemotherapy as well as radiotherapy. In many cases, surgical resection is not possible, and therefore treatment alternatives have to be performed. Chemoradiation has been established as a convincing treatment alternative for locally advanced pancreatic cancer. Carbon ions offer physical and biological characteristics. Due to their inverted dose profile and the high local dose deposition within the Bragg peak precise dose application and sparing of normal tissue is possible. Moreover, in comparison to photons, carbon ions offer an increased relative biological effectiveness (RBE), which can be calculated between 1.16 and 2.46 depending on the pancreatic cancer cell line as well as the endpoint analyzed. Japanese Data on the evaluation of carbon ion radiation therapy showed promising results for patients with pancreatic cancer.Methods and design: The present PHOENIX-01 trial evaluates carbon ion radiotherapy using the active rasterscanning technique in patients with advanced pancreatic cancer in combination with weekly gemcitabine and adjuvant gemcitabine. Primary endpoint is toxicity, secondary endpoints are overall survival, progression-free survival and response.Discussion: The physical and biological properties of the carbon ion beam promise to improve the therapeutic ratio in patients with pancreatic cancer: Due to the inverted dose profile dose deposition in the entry channel of the beam leads to sparing of normal tissue; the Bragg peak can be directed into the defined target volume, and the sharp dose fall-off thereafter again spares normal tissue behind the target volume. The higher RBE of carbon ions, which has been shown also for pancreatic cancer cell lines in the preclinical setting, is likely to contribute to an increase in local control, and perhaps in OS. Early data from Japanese centers have shown promising results. In conclusion, this is the first trial to evaluate actively delivered carbon ion beams in patients with locally advanced pancreatic cancer within a dose-escalation strategy.Trial registration: NCT01795274. © 2013 Combs et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08